Looking at Faces: First-Order and Second-Order Features as Determinants of Facial Appearance. (November 2013) - Rhodes, Gillian
The encoding and relative importance of first-order (discrete) and second-order (configural) features in mental representations of unfamiliar faces have been investigated. Nonmetric multidimensional scaling (KYST) was carried out on similarity judgments of forty-one photographs of faces (homogeneous with respect to sex, race, facial expression, and, to a lesser extent, age). A large set of ratings, measurements, and ratios of measurements of the faces was regressed against the three-dimensional KYST solution in order to determine the first-order and second-order features used to judge similarity. Parameters characterizing both first-order and second-order features emerged as important determinants of facial similarity. First-order feature parameters characterizing the appearance of the eyes, eyebrows, and mouth, and second-order feature parameters characterizing the position of the eyes, spatial relations between the internal features, and chin shape correlated with the dimensions of the KYST solution. There was little difference in the extent to which first-order and second-order features were encoded. Two higher-level parameters, age and weight, were also used to judge similarity. The implications of these results for mental representations of faces are discussed.